Assessing the Role of Microfinance Programs in Enhancing the Socio-Economic Empowerment of Rural Women in Karnali Pradesh, Nepal (Surkhet Journal, 2025)
Microfinance has emerged as a transformative instrument for advancing socio economic development in marginalized communities, particularly among rural women. In Karnali Pradesh, Nepal where economic opportunities are scarce and infrastructure remains underdeveloped women’s entrepreneurial capacity is constrained by limited access to credit, low literacy levels, and socio-cultural barriers. This study investigates the extent to which microfinance programs enhance the economic and social empowerment of rural women entrepreneurs in the region. Using purposive sampling, primary data were collected from 124 women affiliated with microfinance institutions such as Nirdhan Utthan, Mahila Sahayogi, and Chhimek Laghu Bitta. Structured questionnaires captured pre- and post-program indicators. Statistical analyses, including paired sample t-tests, Wilcoxon signed-rank tests, and McNemar tests in SPSS, evaluated changes in business performance, savings, expenditures, asset ownership, decision-making autonomy, mobility, social relationships, education, and health status. Findings reveal significant improvements in both economic empowerments manifested in higher daily sales, customer flow, investment, savings, and asset acquisition and social empowerment, reflected in greater decision-making authority, mobility, social bonds, and access to education and healthcare. The study concludes that microfinance acts as a multidimensional catalyst for women’s empowerment, fostering financial independence and promoting inclusive rural development. It recommends expanding microfinance services alongside integrated training to strengthen entrepreneurial competencies and dismantle structural barriers, thereby contributing to gender equality and sustainable economic growth.